2007
DOI: 10.1111/j.1600-051x.2006.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term periodontal evaluation of impacted canines treated with a closed surgical–orthodontic approach

Abstract: The combined technique permitted the traction of the impacted canines to the centre of the crest, thus simulating a physiological eruption pattern. Correct alignment and good periodontal status were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
68
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 40 publications
1
68
2
5
Order By: Relevance
“…Of the few other studies that have recorded recession very little difference between the operated and unoperated canines has been reported. 15,16 In a retrospective analysis by Zasciurinskiene and colleagues 20 consisting of 32 patients who underwent surgical exposure using the Closed technique, six patients (18.8%) were found to have gingival recession, although the mean values were small and it was not clear at which site the recession was present, nor was the range of the recession quantified. The largest mean value was at the palatal aspect of the canine (0.16mm, SD 0.22), which was not significantly different to the unoperated contra-lateral canines.…”
Section: Discussionmentioning
confidence: 99%
“…Of the few other studies that have recorded recession very little difference between the operated and unoperated canines has been reported. 15,16 In a retrospective analysis by Zasciurinskiene and colleagues 20 consisting of 32 patients who underwent surgical exposure using the Closed technique, six patients (18.8%) were found to have gingival recession, although the mean values were small and it was not clear at which site the recession was present, nor was the range of the recession quantified. The largest mean value was at the palatal aspect of the canine (0.16mm, SD 0.22), which was not significantly different to the unoperated contra-lateral canines.…”
Section: Discussionmentioning
confidence: 99%
“…The eruption of the tooth between the alveolar cortical plates prevents bone dehiscence and unfavorable orthodontic and esthetic consequences. 3,4 Therefore, the most appropriate treatment should simulate the physiologic eruption pattern that occurs at the center of the alveolar ridge, as some authors have suggested. [5][6][7][8] Orthodontic appliances and techniques specifically designed for this purpose have been proposed.…”
mentioning
confidence: 99%
“…[5][6][7][8] Orthodontic appliances and techniques specifically designed for this purpose have been proposed. 4,[8][9][10][11][12][13][14][15] In case of persistent deciduous canines and unerupted permanent canines, the ''tunnel'' technique might be indicated to reproduce the physiologic eruption pattern of the canine. 4,13,14,16 The therapeutic approach to impacted canines is interdisciplinary, with many factors accounting for the final orthodontic and periodontal outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations